Accumulation of heavy metals in different body tissues of Gibel carp - Svecevičius, Gintaras; Idzelis, Raimondas Leopoldas; Mockutė, Eglė (Journal of Environmental Engineering and Landscape Management, 2014)
Heavy metals (HMs) are common persistent pollutants of aquatic ecosystems, which have a property to migrate and accumulate in water organisms. Little information has been compiled on HM accumulation and the interactions between them in fish exposed to their mixtures at environmentally-relevant concentrations. The aim of the present study was to determine accumulation patterns of Cu, Zn, Ni, Cr, Pb and Cd in the muscle, gills and liver of Gibel carp after 14-day exposure to HM model mixture (HMMM) and to Ni separately, at concentrations corresponding to Lithuanian inland water standards (Cu-0.01; Zn-0.1; Ni-0.01; Cr-0.01; Pb-0.005; Cd-0.005 mg/l, respectively). Laboratory tests were conducted on adult Gibel carp under semi-static conditions. The amounts of HMs in the water and body tissues were determined using atomic absorption spectrophotometry (AAS). Heavy metal accumulation order in body tissues of Gibel carp was as follows: muscle > gills > liver. The highest amounts found were of Zn (15.2 mg kg), while the lowest of Cd (0.012 mg/kg). In the muscle and gills, HMs were accumulated in the following order: Zn > Cu > Ni > Cr > Pb > Cd, while in the liver: Zn > Cu > Pb > Ni > Cr > Cd. Meanwhile, the Ni concentration in HMMM-exposed fish liver and gills were significantly higher than in Ni-exposed fish. Data obtained showed that HM accumulation in Gibel carp body tissues was metal and tissue specific, i.e. different tissues showed a different capacity for accumulating HMs. Metals in mixture promoted Ni accumulation in test fish gills and liver under different experimental conditions due to the synergistic effects among them. Although the HM content in Gibel carp different body tissues increased in all cases (average of 49 to 224%) they did not exceed Maximum-Permissible-Amounts (MPA) indicated in the Lithuanian Hygiene Standard.